High‐Yield Production, Characterization, and Functionalization of Recombinant Magnetosomes in the Synthetic Bacterium Rhodospirillum rubrum "magneticum". Issue 9 (23rd July 2021) - Mickoleit, Frank; Rosenfeldt, Sabine; Toro‐Nahuelpan, Mauricio; Schaffer, Miroslava; Schenk, Anna S.; Plitzko, Jürgen M.; Schüler, Dirk
Abstract: Recently, the photosynthetic Rhodospirillum rubrum has been endowed with the ability of magnetosome biosynthesis by transfer and expression of biosynthetic gene clusters from the magnetotactic bacterium Magnetospirillum gryphiswaldense . However, the growth conditions for efficient magnetite biomineralization in the synthetic R. rubrum "magneticum", as well as the particles themselves (i.e., structure and composition), have so far not been fully characterized. In this study, different cultivation strategies, particularly the influence of temperature and light intensity, are systematically investigated to achieve optimal magnetosome biosynthesis. Reduced temperatures ≤16 °C and gradual increase in light intensities favor magnetite biomineralization at high rates, suggesting that magnetosome formation might utilize cellular processes, cofactors, and/or pathways that are linked to photosynthetic growth. Magnetosome yields of up to 13.6 mg magnetite per liter cell culture are obtained upon photoheterotrophic large‐scale cultivation. Furthermore, it is shown that even more complex, i.e., oligomeric, catalytically active functional moieties like enzyme proteins can be efficiently expressed on the magnetosome surface, thereby enabling the in vivo functionalization by genetic engineering. In summary, it is demonstrated that the synthetic R. rubrum "magneticum" is a suitable host for high‐yield magnetosome biosynthesis and the sustainable production of genetically engineered, bioconjugated magnetosomes. Abstract : The synthetic Rhodospirillum rubrum "magneticum", magnetized by transfer of magnetosome gene clusters, is in‐depth characterized with regard to optimal magnetosome biosynthesis. Photoheterotrophic growth conditions are defined that enable high‐yield particle production at moderate temperatures and light intensities. Genetic engineering techniques are finally used to functionalize the particle surface, thereby generating magnetic, catalytically active nanoparticles.